Managing shallow aquifers in the dry zone of Sri Lanka - Sood, Aditya; Manthrithilake, Herath; Siddiqui, Salman; Rajah, Ameer; Pathmarajah, S. (Springer, 2015)
This study looks at the groundwater issues in the dry zone of Sri Lanka and shows how the use of remote sensing with high-resolution images can help in groundwater management. A new approach is developed for automatic extraction of the location of agrowells using high-spatial-resolution satellite imageries. As an example, three pilot sites in three different aquifer systems in the country are considered, and their highresolution images are analyzed over two temporal time periods. The analysis suggests that the well density in all three regions has increased over the last few years, indicating higher levels of groundwater extraction. Using the well inventory developed by this new approach, the water budgeting was prepared for the mainland of Jaffna Peninsula. The analysis shows a wide variation in well density in the Jaffna Peninsula, ranging from (as little as) less than 15 wells per square kilometer to (as high as) more than 200 wells per square kilometer. Calculations made for the maximum allowable water extraction in each administrative division of Jaffna show that less than 3 h of daily extraction per well is possible in some districts. This points to an increasing pressure on groundwater resources in the region and thus highlights the importance of understanding groundwater budgets for sustainable development of the aquifers.